Isolation and characterization of a high-spin mixed-valent iron dinitrogen complex12. Issue 95 (7th November 2018) - McWilliams, Sean F.; Bunting, Philip C.; Kathiresan, Venkatesan; Mercado, Brandon Q.; Hoffman, Brian M.; Long, Jeffrey R.; Holland, Patrick L.
Abstract : A new mixed-valence iron–dinitrogen complex has localized valence by IR and Mossbauer spectroscopies, and slow magnetic relaxation. Abstract : We report a rare example of a mixed-valence iron compound with an FeNNFe core, which gives insight into the structural, spectroscopic, and magnetic influences of single-electron reductions and oxidations. In the new compound, the odd electron is localized as judged from Mössbauer spectra at 80 K and infrared spectra at room temperature, and the backbonding into the N2 unit is intermediate between diiron(i ) and diiron(0) congeners. Magnetic susceptibility and relaxation studies on the series of FeNNFe compounds show significant magnetic anisotropy, but through-barrier pathways enable fairly rapid magnetic relaxation.